Pengembangan Radio Komunikasi VHF A/G Type Icom-A210 - Djunaedi; Rusman; Bahrawi, Ahmad (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
The VHF communication radio type IC - A210 is an air to ground communication radio used by the Lion Air Group airline in carrying out its operations, this device's performance is reduced due to a change in the structure of one of the functions of the transmission cable. To improve the performance of these devices, a remote amplifier is made, so that communication can run normally and problems can be resolved. Remote amplifier is additional equipment intended for VHF communication equipment type IC - A210, this equipment consists of a Mic added with PTT, two amplifiers where one amplifier functions as an information signal amplifier coming from the FOO (Flight Operations Officer) officer on land via the mic then sent to the VHF communication equipment to be transmitted to the aircraft and the other amplifier functions as an information signal amplifier from the VHF communication equipment after receiving a reply from the pilot to be heard by the ground FOO officer. The work of the two amplifiers is alternately arranged using relay components that are regulated from the PTT by the FOO on the ground. The way to operate this Remote Amplifier equipment is the same as how to operate the VHF communication equipment type IC - A210 so that its use does not require special knowledge, so that the officer seems to be using VHF communication equipment directly